PENGARUH PEMBERIAN PUPUK ORGANIK CAIR LIMBAH DAPUR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) - Rantung, Ryan Chrisye; Clara Heinny Supit, Paula; Martje Paulus, Jeanne; Rosadelly Rantung, Meity; Anita Wanget, Sesilia; Engelian Bernadette Inkiriwang, Annatje (Universitas Sam Ratulangi, 2024)
Efforts to increase the productivity of land kale plants with environmentally friendly cultivation techniques are by utilizing kitchen waste to be processed into liquid organic fertilizer which can spur plant growth. This study aims to examine the effect of kitchen waste liquid organic fertilizer (POC) on the growth and production of land kale plants. This research was conducted in Tolok Village, Tompaso District, Minahasa Regency, North Sulawesi. This research began in October to December 2023. The field experiment was arranged in a Randomized Group Design (RAK), with one treatment factor, namely the concentration of kitchen waste POC, consisting of P0 = 0 ml/l (control), P1 = 25 ml/l, P2 = 50 ml/l, P3 = 75 ml/l, and P4 = 100 ml/l. Parameters observed were plant height, leaf length, number of leaves, and plant fresh weight. Data were analyzed using Analysis of Variance (ANOVA) at the 5% test level if testing with the F test is significant, followed by a different test of the means using the BNT (Least Real Difference) test at the 5% level. The results showed that the provision of POC had an effect on plant height, leaf length, number of leaves, and fresh weight of plants. Giving the best kitchen waste POC is at a concentration of 100 ml/liter, which gives the highest results in all parameters observed. Keywords: liquid organic fertilizer, kitchen waste, land kale